Poor Physical Capacity Combined With High Body Fat Percentage as an Independent Risk Factor for Incident Hypertension in Chinese Suburb-Dwelling Older Adults - Han, Peipei; Zhang, Yuanyuan; Chen, Xiaoyu; Liang, Zhenwen; Yu, Xing; Liu, Yuewen; Sang, Sijia; Mao, Jiayin; Liu, Jingxuan; Chen, Wuxiong; Li, Junxue; Cheng, Yazhou; et al. (Frontiers in Public Health, 2022)
Background This study examined the effects of poor physical capacity and high body fat percentage (BF%) on the incidence of hypertension in Chinese suburb-dwelling older adults. Methods This study was conducted on 368 Chinese suburb-dwelling participants aged ≥ 60 years without hypertension (mean age: 66.74 ± 5.59 years, 48.9% men). Poor physical capacity is defined by the Asian Working Group for Sarcopenia (AWGS) criteria as grip strength < 26 kg for men and < 18 kg for women or walking speed <0.8 m/s. High BF% was defined as values that are greater than the upper tertile for BF% as stratified by sex. The outcome was the incidence of hypertension. Results Overall, 5.7% of subjects had both poor physical capacity and high BF%. After the average follow-up duration of 2 years, the incidence of hypertension was 39.7%, and those experiencing both poor physical capacity and high BF% had the highest incidence (81.0%). After multivariate adjustments, the incidence of hypertension was associated with the combination of poor physical capacity and high BF% [odds ratio (OR) = 6.43, 95% CI = 1.91–21.64] but not solely with poor physical capacity (OR = 1.11, 95% CI = 0.55–2.25) or only high BF% (OR = 1.37, 95% CI = 0.80–2.34). Conclusion The combination of poor physical capacity and high BF% can significantly increase the incidence of hypertension in Chinese suburb-dwelling older adults. For hypertension prevention, ideally, we should strive toward decreasing body fat mass while simultaneously improving physical capacity.